Sex Differences in Emotion Recognition and Working Memory Tasks - Saylik, Rahmi; Raman, Evren; Szameitat, Andre J. (Frontiers in Psychology, 2018)
It is proposed that emotional and cognitive functions may be differentiated based on sex. However, it is still unknown whether this assumption could be generalised for all emotional faces and working memory (WM) functions. To examine this, 50 females and 60 males performed an emotion recognition task, consisting of a series of emotional faces as well as three working memory tasks from Cambridge Neuropsychological test battery (CANTAB); namely, spatial working memory (SWM), stocking of Cambridge (SOC), and intra/ extradimensional shifts tasks (IED). The results found that females had faster response times in recognition of both positive and negative faces as compared to males. Furthermore, it was observed that while females were better on SWM task processing, males performed better on IED and four move SOC tasks, illustrating that processing of WM components may differentiate by sex. It has been concluded that emotional and cognitive functions are indeed sensitive to sex differences.